Animals and Medicine The Contribution of Animal Experiments to the Control of Disease - Botting, Jack (Open Book Publishers, 2015)
Animals and Medicine: The Contribution of Animal Experiments to the Control of Disease offers a detailed, scholarly historical review of the critical role animal experiments have played in advancing medical knowledge. Laboratory animals have been essential to this progress, and the knowledge gained has saved countless lives-both human and animal. Unfortunately, those opposed to using animals in research have often employed doctored evidence to suggest that the practice has impeded medical progress. This volume presents the articles Jack Botting wrote for the Research Defence Society News from 1991 to 1996, papers which provided scientists with the information needed to rebut such claims. Collected, they can now reach a wider readership interested in understanding the part of animal experiments in the history of medicine-from the discovery of key vaccines to the advancement of research on a range of diseases, among them hypertension, kidney failure and cancer. This book is essential reading for anyone curious about the role of animal experimentation in the history of science from the nineteenth century to the present.